ADVANCE BOOKING: PRICE DISCRIMINATION OF AIR TICKET - Sud-on, Ploy (Strategic Perspectives on Business and Marketing Management, 2023)
The rise in the number of Low-Cost Carriers has led to a fierce battlefield of the airlines. The competition has come at the expense of yields and profitability as all players has had to lower the fares to compete. This results in a day-to-day airfare fluctuation in order to attract all travellers. In dealing with demand uncertainty, the airlines have offered a choice of Advance-Purchase Discount to secure sufficient seats for both leisure and business travellers. This leaves the question to most travellers, however, on when exactly is the best time to book. This study collected different 5,900 flights operated by 6 major airlines (both low-cost and full-service carriers) in Thai market. Two famous festive events were designated as the departure dates (Songkran and New Year holidays). The study discovered the violation of monotonic property in different areas as fares on booking date closer to departure were found to often lower than those in the preceding booking days. Moreover, according to the fares collected during the period of February 2017 to April 2018, the Low-Cost Carriers were found to consistently provide the lowest airfares.